2018
DOI: 10.1038/s41419-018-0804-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel ADAM-17 inhibitor ZLDI-8 enhances the in vitro and in vivo chemotherapeutic effects of Sorafenib on hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is one of the greatest life threats for Chinese people, and the prognosis of this malignancy is poor due to the strong chemotherapy resistance in patients. Notch pathway components mediate cell survival and epithelial–mesenchymal transition (EMT), and also participate in the induction of multi-drug resistance (MDR). In the present study, we demonstrated the discovery of a novel inhibitor for Notch activating/cleaving enzyme ADAM-17, named ZLDI-8; it inhibited the cleavage of NOTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 59 publications
0
65
0
1
Order By: Relevance
“…In addition, it confirmed that the miR-3163/ADAM-17 axis acts through the Notch signaling pathway. Therefore, our results indicated that miR-3163 may enhance the (1) Jia et al 49 used rhamnetin to inhibit the activation of the Notch signaling pathway and enhance the sensitivity of HCC cells to sorafenib by enhancing miR-34a, which targets Notch protein; (2) Zhang et al 50 identified a novel inhibitor of ADAM-17; and (3) the inhibitors of the presenilin-dependent gamma secretase complex may also be useful in the treatment of HCC [51][52][53][54] .…”
Section: Discussionmentioning
confidence: 80%
“…In addition, it confirmed that the miR-3163/ADAM-17 axis acts through the Notch signaling pathway. Therefore, our results indicated that miR-3163 may enhance the (1) Jia et al 49 used rhamnetin to inhibit the activation of the Notch signaling pathway and enhance the sensitivity of HCC cells to sorafenib by enhancing miR-34a, which targets Notch protein; (2) Zhang et al 50 identified a novel inhibitor of ADAM-17; and (3) the inhibitors of the presenilin-dependent gamma secretase complex may also be useful in the treatment of HCC [51][52][53][54] .…”
Section: Discussionmentioning
confidence: 80%
“…The microtissues were adhered to the surface of the nude mice’s livers using biological-medical gel (Cai-Hong-Yi-Xue-She- Bei Corporation, Kunming City, Yunnan Province, People’s Republic of China). 44 , 45 After four to eight weeks of growth, the mice were harvested. The liver organs with nodules formed by the MDA-MB-231 cells were collected for Masson staining, following the methods described by Shao et al and Xie et al 46 , 47 The photographs of the Masson staining were quantitatively analyzed to determine the relative invasive growth of the MDA-MB-231 cells using the ImageJ software, following the methods descripted by Shao et al and Xie et al 46 48 The thickness of the nodules or liver organs was determined, and the relative invasive growth of the MDA-MB-231 cells in the nude mice’s livers (the nodule thickness relative to that of the liver organ) was calculated as follows: (the nodule thickness of the control group)/(the liver organ thickness of the control group) × 100% or (the nodule thickness of the administration group)/(the liver organ thickness of the administration group) × 100%.…”
Section: Methodsmentioning
confidence: 99%
“…EMT process and HGF/c-MET pathway are foremost molecular mechanisms of antitumor drug resistance, which significantly promotes the antitumor effect of drugs on cancer cells. [67][68][69][70][71][72][73][74][75][76][77] Jiao et al showed that HGF treatment induced gefitinib resistance in human lung cancer cells and miR-1-3 p or miR-206 sensitizes cells to gefitinib by inhibition of c-Met and EMT process. 78 In the present work, we found that ARQ-197 inhibited the EMT process of HCC cells and enhanced the sensitivity of HCC cells to sorafenib.…”
Section: Discussionmentioning
confidence: 99%